Efficacy of esmolol and magnesium sulphate in attenuation of haemodynamic response during laryngoscopy and intubation: a clinical comparative study - Ray, Arbind K.; Lahkar, Babita; Sen, Trina; Bharali, Hrishikesh (International Journal of Research in Medical Sciences, 2018)
Background: Hypertension and tachycardia accompanying laryngoscopy and tracheal intubation are deleterious, especially in patients with cardiovascular or intracranial diseases. The aim of the present study was to compare and evaluate the efficacy of magnesium sulphate and esmolol in attenuating the hemodynamic response to laryngoscopy and endotracheal intubation. Methods: A prospective study was conducted with ninety patients undergoing elective surgery under general anaesthesia who were randomized into three groups of thirty patients each. Group I received 10 ml of 0.9% normal saline, group II received magnesium sulphate 50mg/kg body weight and group III received esmolol 2mg/kg body weight. The study drugs were administered intravenously over 30 seconds, 3 minutes prior to laryngoscopy. Induction was done with sodium thiopentone and endotracheal intubation was performed after one minute of administration of succinylcholine 1.5mg/kg. Heart rate and blood pressure were recorded from preinduction up till 10 minutes after intubation. Results: There was a significant rise in heart rate and blood pressure in group II as compared to group I. Conclusions: Esmolol is a better agent than magnesium sulphate to attenuate hemodynamic response to laryngoscopy and intubation.